PERBANDINGAN SUKUK DAN OBLIGASI (TELAAH DARI PERSPEKTIF KEUANGAN DAN AKUNTANSI) - Indah Purnamawati (Universitas Jember, 2013)
The substance of financial system is to find reasonable solution for existing practical problems. Both of these vehicles, sukuk and conventional bonds, attempt to mobilize the fund from surplus spending unit to shortage spending units.Sukuk investment is often regard as identical with conventional bond. There are fundamental differences between the two.In the conventional bond the underlying asset is money (debt) and in the sukuk the underlying assets is indeed an assets. The two solutions are clearly not identical;the fundamental diference in their structure has great religious difference .The conventional bond are based on debt instrument while Sukuk financing based on equity method. Keywords: Sukuk. Conventional Bond, AAIOFI